Women’s access to managerial positions: an experimental study of leadership styles and gender - Cuadrado, Isabel; Morales, J. Francisco; Recio, Patricia (The Spanish Journal of Psychology, 2008)
This study attempts to test one of the explanations of the scarce representation of women in managerial positions, specifically the one advanced by “role congruity theory of prejudice toward female leaders” (Eagly & Karau, 2002), which appeals to the fact that women get unfavorable evaluations if they adopt male-stereotypical leadership styles. One hundred and thirty-six undergraduate students participated in an experiment with a 2 (Malestereotypical vs. Female stereotypical leadership style) 2 (Male vs. Female leader) design. Dependent variables were leader’s competence, efficacy, and evaluation in a series of traits. It was found that, regardless of sex, the leaders were considered more competent and efficient, and were evaluated more favorably, when they adopted stereotypically feminine leadership styles. Implications of these findings for women’s underrepresentation as leaders in management top positions worldwide are discussed.